Haiti in the balance why foreign aid has failed and what we can do about it - Buss, Terry F.; Gardner, Adam.; ProQuest (Firm) (Washington, D.C. : Brookings Institution Press : National Academy of Public Administration, 2008)
"Tackles such questions as why has assistance been so ineffectual and what can be learned from Haiti's plight concerning foreign aid in general, by analyzing nearly twenty years of Haitian history, politics, and foreign relations"--Provided by publisher.
Introduction -- Haiti in extremis -- Political history -- Foreign assistance -- Foreign assistance and foreign policy -- Foreign assistance failures -- Lessons learned : reforming foreign assistance -- Lessons learned : governance and democracy programs -- Rene Preval's first two years in office : 2006--08.
Includes bibliographical references (p. 207-219) and index.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Economic assistance -- Haiti; Haiti -- Politics and government; Electronic books